Pengembangan Media Pembelajaran Interaktif Berbasis Multimedia pada Mata Pelajaran Tarikh - Lutfiana Romadhan; Darodjat Darodjat (Proceedings Series on Social Sciences & Humanities, 2022)
Date learning materials are generally in the form of text, so an innovation in interactive multimedia-based learning media is needed for date subjects. The purpose of this study was to develop interactive learning media, to find out the evaluation and feasibility of media according to material experts, media experts and educators for interactive multimedia-based learning media on the subject of the main material date (the development of Islam in Indonesia during the Dutch colonial period) at Muhammadiyah Somagede Vocational School and the feasibility of the learning media. This research is a type of Research and Development (RND) research with qualitative and quantitative collection techniques. Qualitative data obtained from the results of the questionnaire in the form of explanations, suggestions from material experts, media experts, and educators. Quantitative data was obtained from the results of the questionnaire test in the form of values 5, 4, 3, 2, and 1 which were converted into qualitative data. The instrument used for data collection in the product development process is a questionnaire. Questionnaires were made for 3 respondents, namely material experts, media experts and educators. The development procedure used uses the ADDIE development procedure (analysis, design, development, implementation, evaluation). The results of research and development use the ADDIE development procedure (analysis, design, development, implementation, evaluation). The analysis phase includes field studies. The design stage includes making flowcharts and storyboards. The development phase of interactive learning media product development, validation and revision. The implementation stage is carried out once in a trial, which is tested on educators. The results of the evaluation of the material experts for stage 1 obtained an average of 4.3 and stage 2 obtained an average of 4.5 in the aspects of learning and content and the total overall score was 4.5 with a very good category. Media experts on programming and display aspects at stage 1 got an average score of 4.9 and at stage 2 got an average score of 5 so that the overall score got an average score of 5 in the very good category. The feasibility of learning media based on trials on date subject educators got an average of 4.9 with a very good category. Thus, interactive learning media on the subject of the subject matter date (the development of Islam in Indonesia during the Dutch colonial period) at SMK Muhammadiyah Somagede is feasible to use.